A phonemic description of the Tobilung language - Buck, Gillian P. (Philippine Journal of Linguistics, 2009)
This paper describes the phonemics of Tobilung, one of the Dusun subgroup of Bornean languages. Tobilung shares many of the characteristics of Austronesian languages, having a relatively small inventory of consonants and vowels, a predominance of disyllabic words and also of consonant-vowel sequences. Features of interest include the relatively uncommon bilabial and alveolar implosives and the juxtaposition of voiced and voiceless bilabial and alveolar plosives in adjacent syllables. Vowel-final words are rare and are only found in minor lexical categories. There is some preliminary consideration of morphophonemics in this paper. In common with other Dusunic languages, Tobilung exhibits vowel harmony, in which morphophonemic processes trigger the change of the 'neutral' '0' vowel to the low 'a', but this process is blocked by geminate vowel clusters within roots. Conversely, there is also 'neutralisation' where at times the morphophonemic processes trigger the change of 'a'vowels to neutral '0'.